GRANULASI ABU LAYANG BATUBARA MENGGUNAKAN KARAGENAN DAN APLIKASINYA SEBAGAI ADSORBEN Pb(II) - Astuti, Widi; Izzati, Indah Nurul (Jurnal Bahan Alam Terbarukan, 2015)
The increase of electrical industry using coal as an energy source resulting in accumulated solid waste such as fly ash.Coal fly ash is mainly composed of some oxides including Al2O3, SiO2 having active siteand unburned carbon as a mesopore material that anables it to act as a potentialadsorbent.However, the use of powder coal fly ash as an adsorbent is quite complex, especially in the filtration installation, so difficult to be applied in the industry.The aim of this study is to carry out granulation of the coal fly ash with the addition of carrageenan as a binder to improve the mechanical and chemical stability thereby increasing the effectiveness and efficiency of the adsorption process. Coal fly ash wasreacted with sodium hydroxide solution and then granulated with the addition of carrageenan 10, 15 and 20 w/w. Granular coal fly ash was further characterized its specific surface area, functional group and morphology. Furthermore, granular and powder treated coal fly ash were tested their adsorption ability for ion Pb (II). The results show that the addition of carrageenan as a binder can change the characteristics of coal fly ash, decrease specific surface area and adsorption capability. The adsorption of Pb (II) by coal fly ash granular follows the Langmuir isotherm model with a constant value of is 0.173 and KLis 0.329.